IDEOLOGI KEPENGARANGAN DALAM BUKU PUISI 99 UNTUK TUHANKU KARYA EMHA AINUN NADJIB - Rabbani, Ilham; Hangganararas, Hatindriya (MIMESIS, 2021)
The poetry book â€œ99 untuk Tuhankuâ€ which was first published in 1983 by Penerbit Pustaka â€“ Perpustakaan Salman ITB Bandung, is the work of Emha Ainun Nadjib (EAN), a well-known writer from Indonesia. The figure of EAN is known for his writings, whether in the form of essays, prose, drama scripts, or poems that are religious, but at the same time critical in looking at the problems of life, including against power in Indonesia. This paper aims to dismantle the EAN Authorial Ideology in poetry book â€œ99 untuk Tuhankuâ€ by using the materialistic literary theory by Terry Eagleton. In dismantling the Authorial Ideology, it will first outline several aspects of external constituents such as the General Mode of Production, Literary Mode of Production, and General Ideology. The research method used is descriptive qualitative. The research results obtained are the Authorial Ideology produced by EAN is humanism-religious and sufism. Meanwhile, the ideology of the New Order regime (General Ideology) is authoritarianism, militarism, and capitalism. The ideology that was contested by EAN, instead of being a resistance ideology for power, has the potential toÂ become an adaptive ideology and potentially perpetuate the dominance of the New Order regime.Â Â